Optimization of Generator Arrangement for Jin-Zhong HVDC - Huifan XIE; Yong MEI; Jian ZHOU; Guanghu XU; Lei HUANG; Ming LI; Xiaobin ZHAO; Jian YANG (Zhongguo dianli)
The paper proposes an optimization method which gives the minimum on-service generator number during the low-water and low-load period on the basis that the power system is safe and stable. The optimization considers three aspects, effective short circuit ratio, stability under island mode and low-order resonance. It is found that the introduction of active DC blocking during isolated operation mode can help effectively eliminate the risk of shortage of short-circuit current, power oscillations and low-order resonance. Operational practice suggests that the minimum on-service generator number of Liyuan and Ahai power plants can be reduced to two respectively when the proposed approach is applied. By reducing the on-service generator number, the risk of having generators operate without load during the low-water and low-load period is alleviated substantially, thus ensuring the safety of equipment of power plants during island mode.